2020
DOI: 10.3390/metabo10100420
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Follicle-Stimulating Hormone and Adiponectin in Postmenopausal Women

Abstract: Beyond fertility, follicle-stimulating hormone (FSH) may exert action on adipocytes, which are the major source of adiponectin and leptin, linking to insulin resistance. Therefore, we evaluated the relationships between FSH and adipocyte-derived hormones. This cross-sectional study enrolled postmenopausal women aged 40–65 years. The variables measured in this study included clinical parameters, fasting levels of sex hormones, glucose, insulin, and adipokines. A total of 261 women without breast cancer, 88 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[ 31 ] Previous studies showed that adiponectin level is negatively associated with estradiol level and positively associated with FSH level. [ 32 , 33 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 31 ] Previous studies showed that adiponectin level is negatively associated with estradiol level and positively associated with FSH level. [ 32 , 33 ]…”
Section: Discussionmentioning
confidence: 99%
“…[31] Previous studies showed that adiponectin level is negatively associated with estradiol level and positively associated with FSH level. [32,33] Few studies have examined the impact of FSH on MetS. In two clinical studies, Stefanska et al examined the association between FSH and MetS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both TMX and estrogen have previously been shown to alter adiponectin signaling in both androgenic and anabolic tissues; to the best of our knowledge, this is the first demonstration of this effect in a myogenesis model at the proteomic level. 24,25 To determine if there were significant functional changes induced by TMX across all myogenically regulated proteins, we next performed STRING and GO enrichment on the subset of proteins that was unique to untreated myogenesis (n = 195) and TMX myogenesis (n = 161), respectively. Functional enrichment showed that the majority of proteins found only in the untreated data set were involved in rRNA processing, whereas the TMX effect was enriched for protein localization to telomeric DNA (Figure 3B).…”
Section: Tamoxifen Induces Changes In Myogenic Adiponectin Signaling ...mentioning
confidence: 99%
“…The study found that overweight menopausal women had higher serum levels of insulin, C-peptide, resistin, leptin and inflammatory factors than normal-weight menopausal women ( Palla et al, 2020 ). In addition, FSH levels were found to be significantly associated with adiponectin and leptin-adiponectin ratio in menopausal women, which may link FSH to abnormal energy metabolism and insulin resistance ( Huang et al, 2020 ). Cohort studies based on Asian women found that obesity is closely related to the incidence and severity of psychological and physical climacteric symptoms ( Lin et al, 2005 ; Kim et al, 2020 ).…”
Section: Epidemiological Characteristics Of Fsh Level and Body Compos...mentioning
confidence: 99%